Surgical learning activities for house officers: do they improve the surgical experience?. (November 2016) - Maweni, R.; Foley, R.; Lupi, M.; Shier, D.; Ronan O'Connell, P.; Vig, S.
Abstract Objective To ascertain whether house officers (HOs) attain a more satisfactory surgical rotation experience when they perform basic surgical learning activities. We also sought to establish how many and which learning activities HOs achieve and the effect on their surgical experience. Methodology A questionnaire listing 20 learning activities and questions regarding satisfaction with an overall experience was disseminated to HOs in the UK and Ireland who had completed ≥3 months of surgical rotations. Satisfaction with surgical experience was dichotomised in order to perform logistic regression using R Studio software v0.98. Results The survey was completed by 150 respondents, with 26 % completing at least 10 basic surgical learning activities during their surgical rotation. On multivariate analysis, the completion of these learning activities was significantly associated with a satisfactory rotation experience (p < 0.001). Furthermore, the use of a checklist of surgical activities provided to HOs was associated with a significant increase in the performance of learning activities (p = 0.003). Conclusion Surgical HOs who were informed about potential basic surgical learning activities that can be performed during their rotations performed significantly more of these activities. And these activities were associated with a significantly greater satisfaction with surgical rotations. Therefore, we recommend facilitating HOs completion of these activities as this will ensure that basic surgical competencies are achieved and that HOs will be more satisfied with their surgical experience.